2008
DOI: 10.1021/ie8007743
|View full text |Cite
|
Sign up to set email alerts
|

Development of a CaO-Based CO2 Sorbent with Improved Cyclic Stability

Abstract: The carbonation of CaO is an attractive method for removing CO2 from hot gas mixtures. However, regeneration and reuse of a CaO-based sorbent causes a gradual decline in absorption capacity, which ultimately limits the life of the material. Various methods have been proposed for increasing the life cycle performance of a CaO-based sorbent. Two of these methods were selected for further investigation. One method incorporates an "inert" material in the sorbent, while a second method stabilizes the sorbent throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 28 publications
7
119
0
Order By: Relevance
“…The effect of thermal pretreatment on multicyclic CaO conversion has been extensively analyzed by Manovic and co-workers in a series of papers [17,19,20] as well as by other authors in the last years [18,[21][22][23]29], being a subject of current debate in the literature [8,24,31]. The influence of preheating temperature, exposition time, type of atmosphere, type of sorbent, presence of additives, pre-hydration, pre-grinding and looping-carbonation conditions is thoroughly analyzed in these works.…”
Section: A Analysis Of Multicyclic Cao Conversion Data For Pretreatementioning
confidence: 99%
See 1 more Smart Citation
“…The effect of thermal pretreatment on multicyclic CaO conversion has been extensively analyzed by Manovic and co-workers in a series of papers [17,19,20] as well as by other authors in the last years [18,[21][22][23]29], being a subject of current debate in the literature [8,24,31]. The influence of preheating temperature, exposition time, type of atmosphere, type of sorbent, presence of additives, pre-hydration, pre-grinding and looping-carbonation conditions is thoroughly analyzed in these works.…”
Section: A Analysis Of Multicyclic Cao Conversion Data For Pretreatementioning
confidence: 99%
“…Generally, Eq. 10 may describe the diversity of behaviors observed for pretreated sorbents in the first cycles [17][18][19][20][21][22] depending on the relative values of a, b and β such as the presence of a maximum of conversion at a certain value of N . This maximum will exist in the case b > a and β < 1 and will be placed at a cycle number N 0…”
Section: Thermally Pretreated Sorbentsmentioning
confidence: 99%
“…They showed that a weight ratio of CaO to Ca 12 Al 14 O 33 of 75 : 25 that is subjected to calcination at 900 o C for 1.5 h is optimal for preparing this sorbent. A CaO conversion of this sorbent was 65% after 50 cycles, when it was carbonated at 650 o C. Albrecht et al [17] suggested that incorporating finely dispersed MgO or of CaO activity during high temperature reactions. They also found that the sorbents subjected to the more severe initial calcination conditions can have higher adsorption capacity after many cycles.…”
Section: Introductionmentioning
confidence: 98%
“…Current directions of research aimed at this goal are the modification/synthesis of Ca-based sorbents [16,17] and reactivation of natural limestone either by steam [18,19] or heat pretreatment [20][21][22][23][24][25][26][27][28]. Lysikov et al…”
Section: Introductionmentioning
confidence: 99%